2020
DOI: 10.3390/en13102649
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Innovative Rotor Modification for a Small-Scale Horizontal Axis Wind Turbine

Abstract: This paper presents the results of the computational fluid dynamics (CFD) simulation of the airflow for a 300 W horizontal axis wind turbine, using additional structural elements which modify the original shape of the rotor in the form of multi-shaped bowls which change the airflow distribution. A three-dimensional CAD model of the tested wind turbine was presented, with three variants subjected to simulation: a basic wind turbine without the element that modifies the airflow distribution, a turbine with a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The authors showed a broad review of using spatial analysis and multi-criteria spatial decision support system to backing the renewable energy sector. However, there are few works of literature that mention the possibility to use Small Wind Turbines (SWTs) [12] for supporting onshore oil production.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed a broad review of using spatial analysis and multi-criteria spatial decision support system to backing the renewable energy sector. However, there are few works of literature that mention the possibility to use Small Wind Turbines (SWTs) [12] for supporting onshore oil production.…”
Section: Introductionmentioning
confidence: 99%